Features of the course urate nephrolithiasis, comorbid with the metabolic syndrome - A. O. Hubar; M. A. Dovbysh; O. M. Mischenko; I. M. Dovbysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is to study the peculiarities of the course of urate nephrolithiasis and urate nephrolithiasis comorbid with metabolic syndrome.